RESILIENSI KELUARGA PADA KELUARGA YANG MEMILIKI ANAK AUTIS - Eunike Apostelina (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
Abstract This study aimed to determine the family resilience in families who have children with autism based on seven dimensions: stressors, strain, relative and friend support, social support, resilience, coping-coherence, and the distress raised by McCubbin, et al. . The method used in this research is descriptive quantitative method equipped with qualitative methods. Participants in this study consisted of 32 families with an autistic child to fill the scale of family resilience and for qualitative consisted of three families with an autistic child. Quantitative determination of samples was selected using purposive sampling techniques. Qualitative determination of the sample was selected using the sampling technique with a maximum variation. Data obtained with the scale of family resilience raised by McCubbin using the Likert scale models. For the qualitative data obtained through interviews, observation, field notes and open questionnaires. The results of quantitative research shows that family resilience in families with an autistic child classified in the category of medium based on the seven dimensions proposed by McCubbin and McCubbin. There are 21 (66%) families who are at medium stressor category, 28 (87.5%) families included in the category of medium strains, 25 (78.1%) fall into the category of families have relatives and friends who support medium, 24 families (75%) included in the category of having social support medium, 15 families (46.9%) fall into the category of families who have family resilience medium, 23 families (71.9%) having a coping-coherence of the medium, and 28 families (87.5%) having a medium distress. The results of qualitative research showed that there were two families who have low family resilience and belonging to a family of medium. These three families have been able to fight for children's education, although not yet optimal. The three families particularly difficult to get social support from neighbors / friends around. This suggests that families with an autistic child are experiencing difficult and tend to feel protective factor in the risk factors through the process of life, making it difficult to achieve adaptation. These three families have a tendency to get family distress. Keywords: family resilience, family, Autism.